Dampak Alih Fungsi Lahan terhadap Kondisi Sosial Ekonomi Petani di Subak Sesetan - SINAGA, RAJA DOLI; SUDARMA, I MADE; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Impact of Land Use Changes on the Socio-Economic Conditions of Farmers in Subak Sesetan The dense population of Denpasar city causes the increasing demand for land. The largest rice field conversion in Denpasar in 2017-2019 occurred in South Denpasar Sub-district, which replaced 268.15 ha of rice fields. Subak Sesetan is one of the subaks which underwent land use change in the area. The conversion of agricultural land for non-agricultural purposes in Subak Sesetan is expected to continue and affect the socioeconomic condition of farmers. This research aims to analyze the impact of land use change on social, economic, technical, and environmental conditions as well as farmers' endeavours in improving the family economy. The method used is descriptive statistics and interactive data analysis techniques with Miles and Huberman model. The result shows the social impact of land use change is characterized by conflict in the communities around the rice fields due to constructions that blocked the water flow. The economic impact of land use change is characterized by changes in farmers' working hours, and land area changes that affect productivity and income. The land use change in Subak Sesetan also impacted the water needed for agriculture. Environmental damage caused by land use change includes polluted water due to household waste and blocked water flow due to garbage.